The drafting of village regulations concerning the management of agricultural water resources - Aan Eko Widiarto; Moh. Fadli; Triya Indra Rahmawan; Marsudi Dedi Putra; Sholahuddin Al-Fatih; Afrizal Mukti Wibowo (Journal of Community Service and Empowerment, 2023)
The government is authorized to carry out agricultural water management in the village. This agricultural water management aims to ensure that water needs are well fulfilled and sustainable for the welfare of village communities. In this case, the Yosowilangun Lor Village Government, Yosowilangun District, Lumajang Regency, seeks to maintain sustainable agricultural water governance through the authority of the Village Government by establishing Village Regulation Number 7 of 2021 concerning Sustainable Agricultural Water Governance. However, based on the analysis of the situation, there are still problems regarding the implementation of Village Regulation 7 of 2021 concerning Sustainable Agricultural Water Governance, especially regarding the institutional structure and culture of the community in carrying out agricultural water governance in the country. Therefore, in order to strengthen the institutional structure. Moreover, the culture of the community in carrying out agricultural water governance in the village, steps are needed to strengthen the institutional management of agricultural water in the village.